Pentingnya Kewirausahaan Pendidikan sebagai Strategi Misi Gereja dalam Mewujudkan Pertumbuhan Gereja yang Holistik - Mangatas Parhusip (Universitas Methodist Indonesia, 2026)
Church growth constitutes a theological reality that is inseparable from the implementation of God’s mission (missio Dei) in the world. Such growth should not be understood merely in quantitative terms, such as an increase in church membership, but rather as a holistic process encompassing the maturation of faith, the formation of Christian character, and the socio-economic transformation of the congregation. As the body of Christ, the church is called to embody tangible signs of the Kingdom of God through integral, contextual, and life-relevant ministries. Within this missiological framework, educational entrepreneurship is viewed as an effective missionary strategy for addressing contemporary socio-economic challenges. This approach integrates faith-based education, congregational empowerment, and life-skills development as expressions of God’s love and justice in practice. This study employs a qualitative method with a descriptive-analytical approach through theological and missiological literature review. The findings indicate that educational entrepreneurship represents a concrete expression of the church’s transformative mission, fostering spiritual, social, and economic growth of the congregation, while affirming the church’s role as an agent of the Kingdom of God in modern society.